2013
DOI: 10.1007/s10815-013-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two distinct levels of oxygen concentration on embryo development in a sibling oocyte study

Abstract: Purpose This prospective randomized study used sibling oocytes of 258 women with ≥8 oocytes to compare the effect of 5 % O 2 versus 20 % O 2 concentrations on embryo development and clinical outcome. Methods Oocytes of each case were divided between incubators with either 5 % or 20 % O 2 concentration. Outcome measures were fertilization, cleavage, embryo quality, blastocyst formation, and implantation, pregnancy and live birth rates. Results Fertilization and cleavage rates were similar in both groups. The 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 28 publications
5
42
1
Order By: Relevance
“…Our results showed that H 2 O 2 treatment did not significantly reduce the rates of 2-cell formation, 4-cell formation, or 8-cell formation ( P > 0.05) but produced a significant decrease in the rates of blastocyst formation ( P < 0.05) (Figure 1), which was similar to phenomena observed in the clinic [29, 30]. Therefore, we considered that treatment with 0.03 mM H 2 O 2 reflected clinical relevance and was suitable for inducing oxidative damage in the treated group.…”
Section: Resultssupporting
confidence: 84%
“…Our results showed that H 2 O 2 treatment did not significantly reduce the rates of 2-cell formation, 4-cell formation, or 8-cell formation ( P > 0.05) but produced a significant decrease in the rates of blastocyst formation ( P < 0.05) (Figure 1), which was similar to phenomena observed in the clinic [29, 30]. Therefore, we considered that treatment with 0.03 mM H 2 O 2 reflected clinical relevance and was suitable for inducing oxidative damage in the treated group.…”
Section: Resultssupporting
confidence: 84%
“…Pregnancies ending with a live birth were 70 % (n=21/30) in IVF group and 85 % (n=29/34) in ICSI group, respectively (p=0.23). [4,18,19]; others reported an improvement in clinical outcomes even though embryo quality was not affected [3,9,[20][21][22]; lastly, some authors observed an improvements in embryo quality without an increase in overall pregnancy results [23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…Results obtained are largely inconsistent. Some papers highlighted benefits in both embryo quality and clinical outcome [4,18,19]; others reported an improvement in clinical outcomes even though embryo quality was not affected [3,9,[20][21][22]; lastly, some authors observed an improvements in embryo quality without an increase in overall pregnancy results [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%